Preliminary Study of Steels Corrosion Phenomena in Liquid Lead-Bismuth using Molecular Dynamics Methods - Alan Maulana; Zaki Su'ud; Hermawan K. Dipojono; Khairurrijal Khairurrijal (Institut Teknologi Bandung, 2007)
One of the prospective coolant material which can be used in the forth generation nuclear reactor is a liquid lead-bismuth. This coolant has inherent safety capability, economical, and able to burn their own nuclear waste. The problem of using this coolant is corrosion phenomena of steel occurred in the interaction with liquid lead-bismuth especially at high temperatures. Corrosion in this study is assumed as diffusion phenomena of leads or bismuths into the surface of steel. This phenomenon have been studied by molecular dynamic methods. As the first step to this investigation, the molecular dynamic program called Moldy has been used to simulate pure iron and lead system. The molecular dynamic simulation result of pure Fe system at 0 K showed that the peaks positions of radial distribution function is in a good agreement with the result from experiment. The deviation of the peaks position resulted from simulation and experiment is about 0.5%. The simulation result of Pb system showed no significant different with the result from experiment. The simulation also shows the broadening of the curves of radial distribution function and lowering the intensity at high temperature. These results indicate that the atomic positions of the system are distributed randomly.